The MMX InfraRed Spectrometer (MIRS) for the spectral characterization of the Martian system - Maria Antonietta Barucci; Pernelle Bernardi; Jean-Michel Reess; Sonia Fornasier; Frederic Merlin; Alain Doressoundiram; Thomas Gautier; Takahiro Iwata; Hiromu Nakagawa; Tomoki Nakamura; Christophe Donny; Sadok Abbaki; et al. (Progress in Earth and Planetary Science)
Abstract MIRS (MMX InfraRed Spectrometer) is a push-broom imaging spectrometer onboard of the JAXA sample return MMX mission. It has been built by the French laboratory LESIA, today LIRA (Laboratory for Instrumentation and Research in Astrophysics) of Paris Observatory-PSL in collaboration with five other French laboratories, collaboration and financial support of CNES and close collaboration with JAXA and MELCO. MIRS, designed to accomplish the MMX scientific objectives, has been built to be adapted on MMX Exploration Module. MIRS will remotely observe the Martian system for three years. MIRS will observe Phobos, Deimos and Mars in the spectral range 0.9–3.6 µm to characterize surface composition of the satellites and investigate Martian atmospheric variations. An overview of the MIRS Flight Model is presented as well as the data processing and the expected results.